A economia solidária como estratégia de resistência ao capital : considerações sobre as experiências da agricultura familiar na Paraíba - Ramalho, Rosângela Palhano (2024)
The solidarity economy is a set of production, commercialization, consumption, credit and service initiatives that operate on the principles of cooperation, self-management and solidarity. Economic goals are achieved by strengthening personal ties, improving the living conditions of those who work and caring for the environment. In the current system of production, labor relations are shaped to guarantee the acquisition of profit, so the capitalist mode of production determines the formation of territories. From this perspective, one can conceive of socio-spatial formation and transformation based on the constitution of solidarity networks of production and distribution. In Brazil, since the 1980s, there has been a significant advance in the solidarity economy. Its dissemination resulted in the creation of a public institutional structure that consolidated the agendas of the solidarity economy movement in the country, directing public policies and giving the activity visibility and relevance. The National Secretariat for Solidarity Economy diagnosed the solidarity economy in Brazil by carrying out two mappings. It was found that solidarity-based economic ventures are found in almost half of Brazil's municipalities, involve more than 1.4 million workers and that the majority of initiatives are in the Northeast and operate in rural areas. In Paraíba, the solidarity initiatives are predominantly from family farming, a vital sector for national agricultural production, for the country's food security and for the formation of peasant territories. In this sense, this work sought to understand how the solidarity practices adopted by the Paraiba family farming sector have transformed local territories and contributed to the strategy of resistance to capitalist accumulation. In order to achieve this objective, a thorough bibliographical and documentary survey was carried out, as well as field research consisting of semi-structured interviews with public managers who implement public policies on the solidarity economy in Paraíba and with family farmers. The results show that the solidarity economy remains a concept under construction, with consensus and divergence at both the theoretical and practical levels. With regard to public policies for the solidarity economy, there was a setback between 2016 and 2022, caused by the dismantling of the national public apparatus to support solidarity practices, which was re-established in 2023. In Paraíba, the instruments of action were maintained and the secretariat responsible for the solidarity economy expanded the number of public support facilities. For family farming, the Food Acquisition Program will continue to be implemented in the form of Simultaneous Donation Purchases, as well as emergency and institutional purchases and support for agro-ecological fairs. It was also concluded that both the solidarity economy and family farming adopt strategies of resistance, and the search for emancipation through work and agro-ecological production are practical examples of contesting the capitalist way of reproducing survival. The search for emancipation through work and agroecological production are practical examples of contesting the capitalist way of reproducing survival. Finally, in the speeches of the research subjects, it can be seen that they recognize not only the relevance of the activity they carry out, but also the social place they occupy, elements that denote the struggle and resistance present in the process of peasant reproduction.